2014
DOI: 10.1007/s11255-014-0751-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium retards the progress of the arterial calcifications in hemodialysis patients: a pilot study

Abstract: Magnesium probably retards the arterial calcifications in hemodialysis patients. Further clinical studies are needed to clarify whether magnesium provides cardiovascular protection to this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…Our study results are consistent with previously published observational and pilot studies in the dialysis and chronic kidney disease populations [9, 1319]. A recent cohort study with a maximum follow up of 10.8 years found that a lower serum Mg was associated with increased mortality in PD patients [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study results are consistent with previously published observational and pilot studies in the dialysis and chronic kidney disease populations [9, 1319]. A recent cohort study with a maximum follow up of 10.8 years found that a lower serum Mg was associated with increased mortality in PD patients [23].…”
Section: Discussionsupporting
confidence: 92%
“…The transient receptor potential melastin (TRPM)7 cation channel as well as the Wnt/β-catenin pathway are proposed as being essential to Mg regulating vascular calcification [7, 11]. Small observational studies and pilot studies administering Mg containing phosphate binders in dialysis populations have found a significant association between lower serum Mg levels and the progression of CAC, peripheral arterial calcification, mitral annular calcification, and atherosclerosis of the common carotid artery [1319]. A recent study demonstrated that a higher serum Mg significantly decreased the mortality risk associated with hyperphosphatemia in HD patients [20] As well, a lower serum Mg level has been found to be associated with increased mortality in both HD and PD patients [2127].…”
Section: Introductionmentioning
confidence: 99%
“…Serum Mg levels in the former group significantly increased from baseline (0. [77]. At the end of the study, the number of patients with improved carotid IMT was significantly higher in the Mg-containing phosphate binder group than in the Ca-containing binder group (P = 0.04).…”
Section: Mg-containing Phosphate Bindersmentioning
confidence: 81%
“…Tzanakis et al have reported the results of a prospec tive randomized trial in which they allocated 72 stable patients on haemodialysis to receive either magnesium carbonate plus calcium acetate as a phosphate binder (magnesium group) or calcium acetate alone (calcium group). 90 They assessed the presence and progression of arterial calcifications during 12 months using plain Xrays and a simple vascular calcification score. They found worsening of arterial calcification in nine of 32 (28%) patients in the magnesium group and in 12 of 27 (44%) patients in the calcium group (P = 0.276).…”
Section: Intervention Studiesmentioning
confidence: 99%